Reseña: Less Is More: How Degrowth Will Save The World de Jason Hickel. (Desarrollo, Estado y Espacio, 2024)
Reseña: Less Is More: How Degrowth Will Save The World. Jason Hickel. Random House. Londres, 2020. Primera Edición. 336 páginas.  ISBN: 978-1-473-58173-9.